Impact of neutron star spin on Poynting–Robertson drag during a type I X-ray burst - Speicher, J; Fragile, P C; Ballantyne, D R (Monthly notices of the Royal Astronomical Society, 2023)
ABSTRACT External irradiation of a neutron star (NS) accretion disc induces Poynting–Robertson (PR) drag, removing angular momentum and increasing the mass accretion rate. Recent simulations show PR drag significantly enhancing the mass accretion rate during Type I X-ray bursts, which could explain X-ray spectral features such as an increase in the persistent emission and a soft excess. However, prograde spin of the NS is expected to weaken PR drag, challenging its importance during bursts. Here, we study the effect of spin on PR drag during X-ray bursts. We run four simulations, with two assuming a non-spinning NS and two using a spin parameter of a* = 0.2, corresponding to a rotation frequency of 500 Hz. For each scenario, we simulate the disc evolution subject to an X-ray burst and compare it to the evolution found with no burst. PR drag drains the inner disc region during a burst, moving the inner disc radius outwards by ≈1.6 km in the a* = 0 and by ≈2.2 km in the a* = 0.2 simulation. The burst enhances the mass accretion rate across the innermost stable circular orbit ≈7.9 times when the NS is not spinning and ≈11.2 times when it is spinning. The explanation for this seemingly contradictory result is that the disc is closer to the NS when a* = 0.2, and the resulting stronger irradiating flux offsets the weakening effect of spin on the PR drag. Hence, PR drag remains a viable explanation for the increased persistent emission and soft excess observed during X-ray bursts in spinning NS systems.